DAMPAK KEBERADAAN PERKEBUNAN PLASMA KELAPA SAWIT PT. RIMBA HARAPAN SAKTI 1 TERHADAP SOSIAL EKONOMI MASYARAKAT DESA PEMATANG LIMAU: Norhalimah Ramadhani1, Endah Panca Wijayanti2, Parissa Swasti Rn3 - Norhalimah Ramadhani; Endah Panca Wijayanti; Parissa Swasti RN (Jurnal Penelitian Agri Hatantiring, 2025)
This study aims to analyze the impact of the existence of oil palm plasma plantations of PT. Rimba Harapan Sakti 1 on the social and economic conditions of the community in Pematang Limau Village. Using a descriptive quantitative approach, this study collected data through field observations, interviews with respondents, and related documentation. The sample in this study consisted of 78 respondents selected by purposive sampling. The results of the study indicate that the existence of plasma plantations has a significant impact on improving the social conditions of the community, where there is an increase in population, increased access to education, and reduced social conflict. On the economic side, oil palm plasma plantations have been proven to be able to increase community income and encourage a shift in livelihoods from the traditional sector to the plantation sector. In addition, there is an increase in asset ownership among the community. The conclusion of this study shows that the existence of plasma plantations has a positive impact both socially and economically on the community of Pematang Limau Village. Keywords: Oil palm plasma plantation, social impact, economic impact, PT. Rimba Harapan Sakti 1, Pematang Limau Village.